Predicting skin sensitization potential of organic compounds based on toxicity enhancement to Tetrahymena pyriformis, fathead minnow, and Daphnia magna. (1st January 2018) - Zhang, Weicheng; Chen, Libao; Yao, Lunguang
Abstract: Skin sensitization is an important occupational health problem and immunotoxicity endpoint. Considering animal welfare and time and cost savings, many alternative approaches, such as those conducted in vitro, in silico, and in chemo, have been proposed and applied to predict skin sensitization of compounds. Toxicologically, sensitizers can elicit excess toxicity at greater levels than non-sensitizers due to their capacity to react with proteins/peptides. Based on this understanding, calculated toxicity enhancements ( T e ) of 65 organic compounds from three in vitro bioassays, i.e. 48-hr ciliate ( Tetrahymena pyriformis ) growth inhibition, and both 96-hr fathead minnow and 48-hr Daphnia magna acute lethal toxicities, were employed to qualitatively and quantitatively predict skin sensitization potencies of the test agents. The sensitivity, specificity, and accuracy reaching 80% strongly suggested toxicity enhancement was an excellent parameter for predicting skin sensitization. Linear regressions of skin sensitization against toxicity enhancement were fitted for each bioassay, and they were improved after the sensitizers were categorized into different reaction mechanistic domains, which, in decreasing order of contribution from T e to sensitization, were SN Ar > SN 1 > MA. These results indicated that toxicity bioassays are useful tools and that T e could be a useful parameter that might be applied to predict skin sensitization.